Impact of continuous positive airway pressure (CPAP) on quality of life in patients with obstructive sleep apnea (OSA). (30th May 2016) - Batool‐Anwar, Salma; Goodwin, James L.; Kushida, Clete A.; Walsh, James A.; Simon, Richard D.; Nichols, Deborah A.; Quan, Stuart F.
Summary: Obstructive sleep apnea is a chronic illness with increasing prevalence. In addition to associated cardiovascular comorbidities, obstructive sleep apnea syndrome has been linked to poor quality of life, occupational accidents, and motor vehicle crashes secondary to excessive daytime sleepiness. Although continuous positive airway pressure is the gold standard for sleep apnea treatment, its effects on quality of life are not well defined. In the current study we investigated the effects of treatment on quality of life using the data from the Apnea Positive Pressure Long‐term Efficacy Study (APPLES), a randomized controlled trial of continuous positive airway pressure (CPAP) versus sham CPAP. The Calgary Sleep Apnea Quality of Life Index (SAQLI) was used to assess quality of life. Overall we found no significant improvement in quality of life among sleep apnea patients after CPAP treatment. However, after stratifying by OSA severity, it was found that long‐term improvement in quality of life might occur with the use of CPAP in people with severe and possibly moderate sleep apnea, and no demonstrable improvement in quality of life was noted among participants with mild obstructive sleep apnea.